A test of the sustainability vision theory: Is it practical? - Nijsiree Vongariyajit (2022)
Since little is theoretically and empirically known about the characteristics of organizational visions that support corporate sustainability, the present study attempts to answer the following questions: (1) What are the characteristics of an organizational vision that promotes sustainability performance? (2) How does such a vision lead to corporate sustainability? The present study examines a Sustainability Vision theory by simulating a retail store environment that comprises Sustainability Vision, Vision Communication, Empowerment of Staff, Motivation of Staff, and Staff Satisfaction variables. A model expressing the relationships among these variables was quantitatively tested by using data from a sample of retail stores in the Bangkok Metropolitan area. Results revealed that visions characterized by brevity, clarity, future orientation, stability, challenges, abstractness and an ability to inspire, and which contain imageries about improving sales, leadership, and customer and staff satisfaction indirectly and directly predict improved store sustainability prospects via Staff Satisfaction. The vision realization variables of Vision Communication, Empowerment of Staff and Motivation of Staff also enhance the vision effects. The present study is among the first few reported studies which identifies vision characteristics supportive of corporate sustainability. It also contributes to the theoretical literature by endorsing the Sustainability Vision theory and offering some directions for further theoretical development. In terms of its contribution to policy and practice, the present study offers some important managerial implications for retail store managers as to how they should espouse a vision that improves the prospect of store sustainability performance.